Focal Dermal Hypoplasia: Case Series - Maria Mansouri; Fatima Zohra Bouzid; Said Amal; Oufae Hocar; Nissrine Aboussair (Wolters Kluwer Medknow Publications, 2023)
Background: Focal dermal hypoplasia (Goltz syndrome) is a genetic multisystem disorder characterized primarily by involvement of the skin associated to face, skeletal, and eyes anomalies. The objective of the present series is to shed light on this rare syndrome and these atypical manifestations. Methodology: Our study reports the case of five Moroccan patients who present typical clinical picture of the Goltz syndrome with some rare manifestations. Results: A total of 5 patients with Goltz syndrome were evaluated. All of them are female with one familial case. The age ranged from 8 months to 35 years. A characteristic Blaschkoid hypo- and hyper-pigmented skin lesions, congenital nodular fat herniation, and skin atrophy were present in all patients. Ocular manifestations were present in 80% of patients. Cranio-facial deformity was seen in 80% of patients. Short stature and intellectual delay were documented in 80% and 40% of patients, respectively. Limb abnormality was found in all patients. Two patients had a cleft lip, one of which unusual lateral facial cleft. Limitations: Genetic testing could not be performed in the present series. Conclusions: Through this work we will discuss the different clinical signs and genetic aspects of Goltz syndrome and the interest of a good clinical expertise.